MySQL Cookbook : solutions for database developers and administrators - Smirnova, Sveta (O'Reilly Media, 2022)
For MySQL, the price of popularity comes with a flood of questions from users on how to solve specific data-related issues. That's where this cookbook comes in. When you need quick solutions or techniques, this handy resource provides scores of short, focused pieces of code, hundreds of worked-out examples, and clear, concise explanations for programmers who don't have the time (or expertise) to resolve MySQL problems from scratch. In this updated fourth edition, authors Sveta Smirnova and Alkin Tezuysal provide more than 200 recipes that cover powerful features in both MySQL 5.7 and 8.0. Beginners as well as professional database and web developers will dive into topics such as MySQL Shell, MySQL replication, and working with JSON. You'll learn how to: Connect to a server, issue queries, and retrieve results Retrieve data from the MySQL Server Store, retrieve, and manipulate strings Work with dates and times Sort query results and generate summaries Assess the characteristics of a dataset Write stored functions and procedures Use stored routines, triggers, and scheduled events Perform basic MySQL administration tasks Understand MySQL monitoring fundamentals.